Characterization of a dual-beam, dual-camera optical imaging polarimeter. Issue 4 (20th April 2020) - Shrestha, Manisha; Steele, Iain A; Piascik, Andrzej S; Jermak, Helen; Smith, Robert J; Copperwheat, Chris M
ABSTRACT: Polarization plays an important role in various time-domain astrophysics to understand the magnetic fields, geometry, and environments of spatially unresolved variable sources. In this paper we present the results of laboratory and on-sky testing of a novel dual-beam, dual-camera optical imaging polarimeter (MOPTOP) exploiting high sensitivity, low-noise CMOS technology, and designed to monitor variable and transient sources with low systematic errors and high sensitivity. We present a data reduction algorithm that corrects for sensitivity variations between the cameras on a source-by-source basis. Using our data reduction algorithm, we show that our dual-beam, dual-camera technique delivers the benefits of low and stable instrumental polarization (<0.05 per cent for lab data and <0.25 per cent for on sky data) and high throughput while avoiding the additional sky brightness and image overlap problems associated with dual-beam, single-camera polarimeters.